Pro-life vs. pro-choice in a resurgent nation: The case of post-Soviet Armenia - Lopatina, Sofia; Kostenko, Veronica; Ponarin, Eduard (Frontiers in Political Science, 2022)
A backlash against liberal gender and sexuality attitudes has been an issue in many societies, especially post-Communist. However, it takes a different shape in each socio–cultural context. This article contributes to academic debates about neo-traditionalism in the post-Soviet space and focuses specifically on Armenia. It points at some possible mechanisms that make these societies look more neo-traditionalist than they actually are. From the previous research of gender aspects of nationalism, we argue that the neo-traditionalist public discourses in Armenia might be a by-product of the national identity construction. We conclude that the individual-choice attitudes in the post-Soviet space may reflect the respondents' acceptance of a national ideology promoted by the post-Soviet elites rather than their private practices. Our aim is to reveal the complexities of neo-traditionalism in the post-Soviet space where everyday practices are at odds with neo-traditionalist narratives, which we argue might be a result of the Soviet legacy of unwritten rules and open secrets.